The Effects of 1-Methylcyclopropene in the Regulation of Antioxidative System and Softening of Mango Fruit during Storage - Li Li; Changbao Li; Jian Sun; Jinfeng Sheng; Zhugui Zhou; Ming Xin; Ping Yi; Xuemei He; Fengjin Zheng; Yayuan Tang; Jiemin Li; Jie Tang (Journal of Food Quality)
The function of 1-methylcyclopropene (1-MCP) in the regulation of quality and antioxidative system of mango fruit was investigated during storage at ambient temperature. Changes in fruit quality, colour, ethylene production, respiration rate, fruit softening enzyme activities, and antioxidative enzyme activities were studied in this study. The results demonstrated that 1-MCP was beneficial for maintaining quality. 1-MCP treatment retarded the decline of firmness, weight, total soluble solid, and titratable acidity, which served as significant parameters for assessing fruit quality in the process of storage. Compared with the fruit of the control group, the treatment with 1-MCP dramatically delayed the colour change of both the pulp and peel and suppressed climacteric peaks of ethylene generation and respiration speed. The significant inducement of peroxidase, catalase, and superoxide dismutase activities were followed by 1-MCP treatment. The fruit treated with 1-MCP displayed significantly inhibited activation of enzymes on the cell wall, i.e., pectin esterase (PE), endo-1,4-β-d-glucanase (EGase), exopolygalacturonase (exo-PG), and endopolygalacturonase (endo-PG), during storage. The results suggested that 1-MCP imposed underlying impact on the maintenance of the softening and extension of postharvest life of mango fruit.